2003
DOI: 10.1289/ehp.6417
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality in relation to biomarkers of pesticide exposure.

Abstract: A study by Nelson and Bunge (1974), noting poor semen quality in fertile men from Iowa City, Iowa, relative to men from New York, concluded, Confirmation of our findings would imply that some unknown factor has caused a decrease in male fertility potential as measured by semen analysis.Although the question of a possible decline in semen quality has been widely studied (Carlsen et al. 1992;Swan et al. 1997), before 2003 no other study included a population drawn from an agrarian environment similar to that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
171
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 389 publications
(177 citation statements)
references
References 30 publications
6
171
0
Order By: Relevance
“…Two reports have indicated that ACM is rarely detected in the general US population. Swan et al (2003) detected ACM in only 21% and 8% of urine samples from men in Missouri and Minnesota, respectively, with LODs similar to this study. Further, in CDC's Third National Report on Human Exposure to Environmental Chemicals (CDC, 2005), ACM was detected in fewer than 5% of the total samples analyzed.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Two reports have indicated that ACM is rarely detected in the general US population. Swan et al (2003) detected ACM in only 21% and 8% of urine samples from men in Missouri and Minnesota, respectively, with LODs similar to this study. Further, in CDC's Third National Report on Human Exposure to Environmental Chemicals (CDC, 2005), ACM was detected in fewer than 5% of the total samples analyzed.…”
Section: Discussionsupporting
confidence: 85%
“…Glutathione-derived mercapturate metabolites of alachlor and metolachlor have been identified as important human urinary metabolites after occupational exposures (Driskell et al, 1996;Driskell and Hill Jr., 1997). By analogy, acetochlor mercapturate (ACM) has been hypothesized to be a human urinary metabolite of acetochlor (Swan et al, 2003;Olsson et al, 2004;Curwin et al, 2005). Human exposure to alachlor has also been estimated by quantifying the hydrolysis product of alachlorrelated metabolites, 2,6-diethylaniline, in urine (Driskell et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, declining androgens (22,26) and decreased sperm production have been shown in laboratory rodents exposed to atrazine as well (22,26,42), albeit at higher doses. Furthermore, atrazine exposure is highly correlated (P < 0.009) with low sperm count, poor semen quality, and impaired fertility in humans (43).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The present study provides sufficient evidence concerning that there is a strong relation between exposure of pesticides and male semen quality.All parameters of semen analysis showed significant difference between the exposure more than 5years and exposure less then 5 years.Some studies have shown definate reletionship with exposure of Pesticides including DDT,Organophpsphorus and mixtures of herbicides, fungicides and incsecticides and decline in sperm count, motility, morpholgy. 19,20 In the present study TFSC of the groupII is less as compare to group I.As TFSC grade the overall sperm quality objectively. The careful examination of semen parameters reveals that the TFSC value is an integrative form of three main parameters viz.Total concentration, motility and normal percentage of sperm morphologies.…”
Section: Discussionmentioning
confidence: 44%